บทบาทและกระบวนการให้สถานภาพแก่บุคคลและสถาบันในรายการ ตลาดสดสนามเป้า - พรพิสุทธิ์ ศรีธรานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To study a role and process of status conferral in variety television program "Taladsod Sanampao". This qualitative research is conducted under a framework of status conferral and variety show television program. In addition, the research also takes into consideration a production process and impact of status conferral. The data are collected from records of the program broadcasted during June-October 2009, in-depth interview with key informants, and documents. The research finding shows that 1. "Taladsod Sanampao" television program takes the role of status conferral through its contents and formats which combine information and entertainment into a variety program. The program presents informative knowledge, as its content, while using entertainment strategy through presentation techniques: 1) host, 2) guest, 3) atmosphere, and 4) form of presentation as its format. Moreover, it is found that a role of status conferral of the program also help enhance status accrues to persons, products or stores, occupation, and markerts through following processes: 1) presented by media 2) presented through media s opinion, 3) presented with celebrity and 4) guaranteed by testimony. 2. In production process, planning is significant in building confident status for the program through choosing of contents which are going to be presented. Furthermore, pre-production process such as source checking is significant to maintain status of the program. 3. Status conferral has effects on persons of stores that are presented in the program as it is found that the persons or stores become widely known and have better status. In addition, in term of impacts on audiences, analyzed from audience s opinions on internet, it is indicated that the program has persuasive effects on audiences, influencing them to want to go to the stores presented in the program and at the same time audiences also have confidence toward status of Taladsod Sanampao TV. Program.